0083 A Thermoregulated Pillow Improves Sleep: Results from Real-Life Data. (25th May 2022) - Testa, Damien; Stoikovitch, David
Abstract: Introduction: Sleep is regulated by homeostatic mechanisms and circadian rhythms.Thermal environment is one of the most important factors that can affect human sleep. This real-life study aims to evaluate the effects of temperature regulation on sleep quality using a thermoregulated pillow. Methods: The Moona device has been used to control the temperature of a pillow pad from 64°F to 95°F. Users with more than 7 uses of the device and who completed the initial questionnaire (18 profile questions) participated in this study from October 2019 to July 2021. Participants rated their sleep quality on a scale of 1 to 5. Comparison between the sleep quality before the first use and the average of the last seven uses of the device has been done. A survey has been sent to all users from June to November 2021. To date, 206 answers have been collected including 32 users who reported having been diagnosed with insomnia. Improvement of their insomnia has been assessed by a 5-point scale (from 'much better' to 'much worse'). Statistical analyses have been performed on Python 3.7. Mean comparisons have been measured by student t-test. Results: The sleep quality significantly increased with the use of the device from 2.6/5 to 3.7/5 (p<0.001) in the general population (N=620). This significant difference has been also measured in several subgroups who have temperature issues. That is the case for overweight/obese users (N=321, from 2.6/5 to 3.7/5, p<0.001), women over 45 (N=97, from 2.4/5 to 3.6/5, p<0.001) and users who feel hot during the night more than several times a week (N=523, from 2.5/5 to 3.8/5, p<0.001). Moreover, 30 out of 32 insomniacs have reported an improvement of their insomnia since using this active cooling pillow pad. Conclusion: The present study findings showed that an active thermoregulated pillow could improve sleep of insomnia patients and several subgroups of patients with issues at controlling temperature at night. Support (If Any):